(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Colonisation was carried out primarily through violence, and Australia was no exception to this. The Europeans used various forms of violence – both physical and psychological – to subjugate, control and rule over the Australian Aborigine people. As the entire colonial administration used violence, the police system too was violent. As the entire police administration was prejudiced against the Australian natives, custodial deaths of the natives were frequent. Jack Davis’ Barungin explores the cruelty of police towards the natives which often resulted in the deaths of natives and reveals how the police were not held accountable for these deaths.